Identity Salience for Latino Male Collegians at Hispanic Serving Institutions (HSIs), Emerging HSIs, and Non-HSIs. (July 2018) - Garcia, Gina A.; Patrón, Oscar E.; Ramirez, Jenesis J.; Hudson, Lisanne T.
This article challenges the notion of underachievement of Latino male collegians by examining those who successfully enter higher education. Using in-depth interviews, we analyze the way three different institutional types contribute to the racial/ethnic identity salience of Latinos, looking specifically at the curricular and co-curricular structures available at a Hispanic Serving Institution (HSI) and emerging HSI in comparison with non-HSIs. Findings reveal differences in identity salience based on the college context.